Pengembangan E-Modul Turbin Angin (Savonius Heliks) dengan Model 4-D Pada Mata Kuliah Energi Terbarukan di Prodi Pendidikan Teknik Mesin Universitas Sebelas Maret Surakarta - Topan Yuli Susilo; Ranto Ranto; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
Renewable energy technologies are currently being developed, one of which is wind turbines. There are two types of wind turbines, namely the vertical axis and the horizontal axis. One of the horizontal wind turbines is the helical savonius. The development of this technology can help the development of renewable energy. The Mechanical Engineering Education study program is testing wind turbines to help students understand wind turbine technology. Through this research a practicum module will be created to assist students in carrying out wind turbine practicum.This electronic module validates the material and media. The results of the material validation stated the suitability of the material in accordance with the material on wind turbines that had been taught in wind turbine courses. The results of the media validation state that the design is attractive and easy to read so that students can understand the electronic module.